Corrosion of bare and galvanized steel in gypsum - Gómez, Mercedes; Andrade, Carmen (Materiales de Construcción, 1988)
Gypsum is a relatively low-cost building material much abounding in our country. When it is put in contact with steel, it may produce high corrosion rates due to its pH value (close to 7). This work reports the results obtained in studying the corrosion rates of bare and galvanized steel in contact with gypsum and plaster, as well as the influence curing thermal treatment applied to gypsum, enviromental relative humidity and addition of compounds with different natures and purposes may have in such process. In-situ observations, as well as the measurement of the Polarization Resistance and the weight loss have been used as measurement technics. From the results obtained it has been possible to deduce that galvanized steel has better behaviour in dry enviroments than bare steel in the same conditions and moist atmosphere induces proportionally more corrosion in galvanized steel than in bare one. Additions to gypsum do not modified these conclusions, though it may be pointed out that addition of nitrites or lime improves the behaviour of bare steel, while galvanized behaviour is not modified. The addition of lime is not recommended because phenomena of dilated along time expansion may take place.